“Pageantry of aggression”: QAnon, animality, and the violent pursuit of whiteness - Corman, Lauren (Frontiers in Communication, 2024)
While the specifics of the far-right COVID-denying QAnon movement may remain cloudy within popular consciousness, in contrast, many can easily conjure the image of Jacob Chansley, the so-called “QAnon Shaman,” when evoking the January 6th US Capitol riot. Chansley, face-painted in the American flag and draped in faux regalia—a virtual menagerie of animals: coyote, buffalo, and eagle—appears clearly, spear in hand, as if parting the fog of war. Photos of Chansley howling or brazenly posing on the Senate dais are indelibly sketched into our collective memory. Some may conjure him simply as a buffoon, but his trespassing and seditious antics are interwoven with a costume that pulls at the long thread of European and American colonialism. This article posits that Chansley’s animalized insurrectionist attire and his ability to play at the borderlands between human and animal, civilized and uncivilized, was an enactment of white supremacy. Insulated by conjoined racist and speciesist legacies, his ensemble placed him closer not only to Western constructions of nature, but also to animality, all without threatening his human status. Working at the intersections of critical race theory and critical animal studies, and illustrated with mainstream news accounts, this article considers broader cultural contexts that reveal Chansley’s sartorial representation as anything but benign.